ABOUT TRANSLATIONS OF PROSE WORKS FROM UZBEK TO GERMAN - Sodiqov Dilshodbek Kobilovich (American Journals, 2024)
Translating prose may initially appear simpler than translating poetry, but it is a specialized skill that goes beyond mere language proficiency. Prose, like poetry, demands talent and a command of literary devices and creative imagery. Just as not everyone who can write becomes a writer, not everyone who knows a language can translate a prose work. Literary translation is a field of artistic creativity. Because, unlike other areas of translation, literary translation has its own characteristics. These features come from the nature of fiction.
Keywords: Prose translation, artistic translation, artistic image tools, fiction.